Strategic Planning Promosi Pariwisata Museum DPR di Era Digital - Sukirno, Zakaria Lantang; Haroni, Nanang (Rumah Jurnal UNEJ, 2022)
Museum is one of tourism destination that faces a huge challenge in this digital era and that happens on DPR Museum at Jakarta. To face that challenge, it needs a promotion strategy applying digital marketing. How is Museum DPR tourism promotion strategy in this digital era? This research based on concepts of strategic planning, SOSTAC (Situation analysis, Objective, Strategy, Tactics, Actions, Control), tourism marketing, and digital marketing. For the methodology, this research uses interpretive paradigm, political significant sampling with the Head of Museum Association as the informant, and domain analysis as the data analysis technique. The result describes that the strategic planning and SOSTAC applied have not been ideal because of the problem that has been experienced by the DPR Museum.